2016
DOI: 10.1042/bst20160125
|View full text |Cite
|
Sign up to set email alerts
|

EML proteins in microtubule regulation and human disease

Abstract: The EMLs are a conserved family of microtubule-associated proteins (MAPs). The founding member was discovered in sea urchins as a 77-kDa polypeptide that co-purified with microtubules. This protein, termed EMAP for echinoderm MAP, was the major non-tubulin component present in purified microtubule preparations made from unfertilized sea urchin eggs [J. Cell Sci. (1993) 104, 445–450; J. Cell Sci. (1987) 87(Pt 1), 71–84]. Orthologues of EMAP were subsequently identified in other echinoderms, such as starfish and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 34 publications
0
19
0
1
Order By: Relevance
“…For example, amacrine‐specific genes would be predicted to be present in the lower half of the INL and in ~40% of the GCL, while amacrine subtype‐specific genes might be present only in a subset of INL neurons. Four genes robustly displayed one of these patterns by lacZ staining: echinoderm microtubule‐associated protein‐like 2 ( Eml2 , Fry, O'Regan, Montgomery, Adib, & Bayliss, ), fibroblast growth factor 3 ( Fgf3 , Represa, Leon, Miner, & Giraldez, ), Phf24 , and Dbn1 . To further explore these patterns, we focused our analysis on Dbn1 .…”
Section: Resultsmentioning
confidence: 99%
“…For example, amacrine‐specific genes would be predicted to be present in the lower half of the INL and in ~40% of the GCL, while amacrine subtype‐specific genes might be present only in a subset of INL neurons. Four genes robustly displayed one of these patterns by lacZ staining: echinoderm microtubule‐associated protein‐like 2 ( Eml2 , Fry, O'Regan, Montgomery, Adib, & Bayliss, ), fibroblast growth factor 3 ( Fgf3 , Represa, Leon, Miner, & Giraldez, ), Phf24 , and Dbn1 . To further explore these patterns, we focused our analysis on Dbn1 .…”
Section: Resultsmentioning
confidence: 99%
“…Centrosome-Primary Cilia Phenotype EML1 has a cell-cycle-dependent localization in mouse neuronal progenitor cells in vitro (Kielar et al, 2014). It co-localizes with the microtubule network in interphase Vero cells (Kielar et al, 2014); however, a ciliary localization has not been described for this protein family (Fry et al, 2016). Its localization was hence further explored in aRGs, as well as in ciliated RPE1 cells, using exogenous expression of an EML1-tagged plasmid, since there are no known reliable antibodies to detect the endogenous protein.…”
Section: Subcellular Localization and Eml1-interacting Proteins Shed mentioning
confidence: 99%
“…In the second study, the structure of the coiled-coil region of EML2 and EML4 revealed that these regions were required for trimeric oligomerisation, and this was named the trimerisation domain (TD) [ 15 ]. It is through the TD and the basic region that EML proteins are able to associate with microtubules, although it is not yet known whether this is through direct binding or via oligomerisation [ 15 , 16 ]. In addition, the TAPE domain is able to bind soluble α/β-tubulin heterodimers through its concave surface, but again, further work is required to understand the importance of this interaction [ 14 ].…”
Section: Human Eml Family and Eml4mentioning
confidence: 99%